Percentage of Flower and Fruit Fall, and Red Chili Production in Ultisol Applied Biostimulants and Inorganic Fertilizers - Shabilla Amartiya Sari; Nuni Gofar (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2023)
Ultisol has main problem of low nutrient availability causing a high percentage of flowers and fruit fall and reducing red chili production. This study aimed to find out effectiveness of biostimulants in reducing percentage of flower and fruit fall, use of inorganic fertilizer doses, and their role in increasing production red pepper in Ultisol. The method used experimental and randomized block design with 9 treatments.  The treatment used application of flush biostimulants and without watering into soil with various doses inorganic fertilizers. The fertilizer doses were 100%, 75%, and 50% based on fertilization recommendations. The study results showed that application of biostimulants combined with inorganic fertilizers of various doses had a significant effect on fruit weight/plant and red pepper production, but had an insignificant effect on the percentage of flowers and  fruits, as well as number of fruits/plant. Application of biostimulants and various doses of inorganic fertilizers tended to increase fall of flowers, number of  fruits/plant, and the percentage of fruit fall. Biostimulants combined  with  inorganic fertilizers were able to reduce fertilizer use as much as 50%.  Production of red pepper with application of biostimulants and 50% of inorganic fertilizers reached 5.36 tons/ha. The results of the economic feasibility analysis of red chili peppers were 1.69 R/C and 0.69 B/C ratio, meaning that the cultivation of red chili with application of  biostimulants was profitable and worthy of development.  So, application of  biostimulants is able to reduce fertilizers by 50% and increase production of red peppers.